The prognostic significance and Immunomodulatory role of SCGB3A1 expression in stage I lung adenocarcinoma - Xin Zhang; ShiNing Li; Yujin Lv; XinYu Liu; Yong Ao; LeQi Zhong; Yi Hu (BMC Medical Genomics)
Abstract Background Many early-stage lung adenocarcinoma patients experience recurrence or metastasis after surgery, and the efficacy of targeted therapies remains suboptimal, significantly impacting the prognosis of these patients. Our study aims to investigate the impact of SCGB3A1 on the prognosis of lung adenocarcinoma patients and its role in immunity. We propose that SCGB3A1 may offer a novel treatment approach for lung adenocarcinoma patients who do not respond well to targeted therapies. Methods We obtained RNA sequencing data from 539 lung adenocarcinoma samples, 59 normal tissues, and 2 metastatic cancer tissues from The Cancer Genome Atlas database. Using Venn diagrams, we analyzed the expression of SCGB3A1 and other differentially expressed genes (DEGs) in different patient groups. Additionally, we performed another Venn diagram analysis to explore the association between SCGB3A1 and immune-related genes. We investigated the relationship between SCGB3A1 expression and patient clinical-pathological data and prognosis. Furthermore, through GO, KEGG, and GSEA enrichment analyses, we explored the functional roles of SCGB3A1 and its association with immune cell infiltration and immune checkpoint genes. The role of SCGB3A1 in LUAD was investigated by cytological experiments. Results The results indicated that SCGB3A1 is associated with both prognosis and immunity. In lung adenocarcinoma, SCGB3A1 may function as a tumor suppressor gene. The high-expression group of SCGB3A1 exhibited a better prognosis and more pronounced immune cell infiltration. Additionally, SCGB3A1 was associated with smoking status and tumor size. A multivariate Cox regression model suggested that SCGB3A1 expression, pathological type, and ethnicity independently impact patient prognosis. Functional enrichment analysis indicated that SCGB3A1 was related to tumor progression, cell proliferation, and immune suppression. Furthermore, ssGSEA analysis revealed that SCGB3A1 expression is associated with immune cell infiltration and tumor-related immune genes. Experimental validation suggested that the overexpression of SCGB3A1 suppressed cell proliferation, migration, and invasion of LUAD. Conclusions In summary, this study investigated the association between SCGB3A1 and the prognosis of early-stage lung adenocarcinoma. The findings revealed that SCGB3A1 is related to immune cell infiltration and tumor-related immune gene expression, which may provide insights into the role of SCGB3A1 in immunotherapy. The cytological experiments indicate that SCGB3A1 is a potential therapeutic target for LUAD.